Sztuka jako narzędzie budowania relacji między człowiekiem a naturą - Czerwińska, Kinga (Studia Etnologiczne i Antropologiczne, 2017)
The article focuses on art understood as a tool for building relationships between man and nature, and the resulting participation of man in nature. The character of this tool, that is art, is dependent on the development of philosophical thoughts and the level of civilization, and has changed together with the development of culture. Recently, under the influence of the progressive degradation of the natural environment, artistic activities are ecologically oriented. However, it is an observable fact that the “taming” of nature through art makes one function more easily in the existing reality.